The crucial role of complementarity, transparency and adaptability for designing energy policies for sustainable development. (December 2021) - Pahle, Michael; Schaeffer, Roberto; Pachauri, Shonali; Eom, Jiyong; Awasthy, Aayushi; Chen, Wenying; Di Maria, Corrado; Jiang, Kejun; He, Chenmin; Portugal-Pereira, Joana; Safonov, George; Verdolini, Elena
Abstract: The UN Sustainable Development Goals (SDGs) and the Paris Agreement have ushered in a new era of policymaking to deliver on the formulated goals. Energy policies are key to ensuring universal access to affordable, reliable, sustainable, and modern energy (SDG7). Yet they can also have considerable impact on other goals. To successfully achieve multiple goals concurrently, policies need to balance different objectives and manage their interactions. Refining previously contemplated design principles, we identify three key principles - complementary, transparency and adaptability - as highly pertinent for multiple-objective energy policies based on a synthesis of seventeen coordinated policy case studies. First, policies should entail complementary measures and design provisions that specifically target non-energy objectives ( complementarity ). Second, policy impacts should be tracked comprehensively in both energy and non-energy domains to uncover diminishing returns and facilitate policy learning ( transparency ). Third, policies should be capable of adapting to changing objectives over time ( adaptability ). These principles are rarely considered in current policies, implying the need to mainstream them into the next generation of policymaking by pointing to best practices and new tools. Highlights: We synthesized seventeen coordinated energy policy case studies. We identify three key principles for multiple-objective energy policies. These principles are complementarity, transparency and adaptability . These principles are rarely considered in current energy policies. There is a need to mainstream them into the next generation of energy policymaking.